PENGARUH CURRENT RATIO DAN TOTAL ASSET TURNOVER TERHADAP GROSS PROFIT MARGIN SELAMA PANDEMI COVID-19 PADA PERUSAHAAN SUB SEKTOR HOTEL, RESTORAN DAN PARIWISATA - Izzah, Elza Nurul (Universitas Prof.Hazairin,SH Bengkulu, 2022)
This study aims to determine the effect of the Current Ratio and Total Asset Turnover on Gross Profit Margin during the COVID-19 pandemic. The variables used in this research are Current Ratio, Total Asset Turnover and Gross Profit Margin. This research was conducted on hotels, restaurants and tourism sub-sector companies listed on the IDX during April 2020-September 2021. The method used is quantitative, with an associative approach, the measurement scale is the ratio scale. The sampling technique used was purposive sampling and the data collection technique was the secondary data source. The results of the Current Ratio test have a significant effect on Gross Profit Margin with a significance of 0.001 < 0.05 and tcount > ttable (3.373 > 1.991). Total Asset Turnover has a significant effect on Gross Profit Margin with a significance of 0.042 <0.05 and tcount > ttable (2,071 > 1,991). And Current Ratio and Total Asset Turnover have a significant effect on Gross Profit Margin with a significance of 0.003 < 0.05 and Fcount > Ftable (6.456> 3.115). The contribution of the variable current ratio and total asset turnover to the gross profit margin is 14.4%